Education and Legal Assistance for Copyright Assessment of the Oral Tradition of Making Fish Bubu (Fishing Trap) in Indigenous Peoples - Pariela, Marselo Valentino Giovani; Saija, Ronald; Pical, Venda Jolanda; Demmatacco, Triska (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Legal education and assistance is important in reviewing copyright regarding the oral tradition of making fish traps which has been passed down from generation to generation in the indigenous communities of Ambon Island. This service focuses on protecting local intellectual property and traditional wisdom contained in the process of making fish traps.Purposes of The Devotion: The purpose of writing this article is to provide education and legal assistance to the people of Asilulu, Central Maluku Regency regarding the study of copyright regarding the oral tradition of making fish traps to improve the health of the people of indigenous countries in the future.Method of The Devotion: Socialization and discussion about the importance of completing documents in registering Intellectual Property Rights for the Oral Tradition of Bubu Ikan at the Ministry of Law and Human Rights, as well as education provided to Village Officials and the Community regarding the completeness of registration documents for registration of Intellectual Property Rights for the Oral Tradition of Bubu Ikan.Results Main Findings of the Devotion: Education and assistance for the protection of traditional knowledge (oral traditions regarding the creation of traditional fish traps) can prevent the cultural identity of the community that owns it from being lost in line with the extinction of traditional knowledge in the future.